Factors Associated with Appropriate Hepatocellular Carcinoma (HCC) Screening Among Chronic Hepatitis C (HCV) Patients with Cirrhosis at an Urban Safety-net Hospital System. (4th October 2017) - Cabrera, Nicolo; Burke, Kerianne; Huhn, Gregory; Go, Benjamin; Winston, Crystal; Adeyemi, Oluwatoyin
Abstract: Background: Despite guidelines recommending liver ultrasound (US) every 6 months for HCC screening in cirrhotic patients with HCV, reported screening rates remain low. Our study evaluated (1) timely screening among patients with HCV cirrhosis identified by transient elastography (FibroScan [FS]) and (2) described factors associated with lack of screening. Methods: All HCV patients with score ≥12.5 kPa (cirrhosis) on FS obtained 3/27/2014- 4/30/2016 for evaluation for HCV treatment within 6 months of index FS by a gastroenterology (GI) or infectious disease (ID) provider within the Cook County Health and Hospitals System were identified. Patient and provider factors and screening were determined through retrospective chart review. Relative risks (RR) for screening failure at 6 months and 12 months after index FS were calculated. Results: Among 243 patients, 64% were men and 38% were co-infected with HIV. Median age was 57 years (range 31 to 79). Median FS score was 21.1 kPa (12.1 to 75). ID requested the index FS in 47%; GI, 47%; and primary care, 5%. In the first 6 months after index FS, 54% underwent US screening; 40% did not have US scheduled; 4.9% had their US cancelled; and 1.2% were scheduled but did not show. Among 112 patients not screened in the first 6 months, 39% underwent US in the subsequent 6 months, 55% were not scheduled for one and 5.4% were scheduled but did not show. At 12 months 72% of all patients were screened. Screening rates at 6 months were significantly higher for index FS obtained in 2015 (62%) compared with in 2014 (44%; P = 0.018) but not in 2016 compared with 2015. Comparing GI vs. ID, RR for screening failure at 1 year was 0.51 (95% CI 0.33-0.80, P = 0.003). Conclusion: In patients with HCV cirrhosis, failure to obtain timely HCC screening was prevalent and driven by failure to order or schedule imaging. ID management was associated with a higher risk of failure of timely screening. Algorithms to improve HCC screening rates will be vital as more ID providers take on a greater role in HCV care. Disclosures: All authors: No reported disclosures.